Perbedaan Latihan High Intensity Ground Walking Dan Latihan Static Bicycle Terhadap Kapasitas Latihan Pada Penderita PPOM - Setiawan Setiawan; Nur Basuki (Interest : Jurnal Ilmu Kesehatan, 2016)
Abstract: High-Intensity Ground Walking, Static Bicycle exercise, exercise capacity, the 6-minutes walking test, chronic obstructive pulmonary disease (COPD). This study aimed to compare the benefits between High-Intensity Ground Walking exercise and Static Bicycle exercise on exercise capacity in patients with chronic obstructive pulmonary disease (COPD). This research is a quasi-experimental study design with two groups pre and post-test design. The subjects were all patients COPD with a moderate and severe degree in The Special hospital of Pulmonary dr. Ario Wirawan Salatiga, that meet the inclusion and exclusion criteria. The data was collected directly by assessing the results of the six-minute walk test before and after the treatments. Data collected were analyzed using SPSS 11.5. The different test within groups measured with the Wilcoxon test, and for between groups measured with Mann Whitney test. The significance level was set on 0.05. Results and Conclusion (1) High-Intensity Ground Walking exercises improve exercise capacity in patients with COPD (p = 0.005), (2) Static Bicycle training program improves exercise capacity of patients with COPD (p = 0.005), (3) There is no difference between High-Intensity Ground Walking Exercise and Static Bicycle training in improving exercise capacity in patients with COPD (p = 0.970).